The Effect of The Religious Tourism of Menara Kudus on Community’s Economy - Amalia, Zulfa; Tyas, Wido Prananing; Putra, J Kevin (Universitas Negeri Semarang, 2020)
The potential of sharia religious tourism is growing along with the increasing Muslim population of the world. Religious tourism is expected to meet the needs of the community for tourism and employment. Thus the development in the field of tourism has the ultimate goal of increasing people's income which has an impact on improving the people's economy. One of the religious tourism areas in Kudus Regency is Menara Kudus tourism area. This area includes the attractions of the Menara Kudus or Kudus Tower, Menara Kudus Mosque (Al Aqsa Mosque) and the tomb of Sunan Kudus. The effect arising from the existence of Menara Kudus is the growth of community economic activities namely traders, craftsmen and service providers. The Religious Tourism of Menara Kudus also improves the community's economy as indicated by an increase in income and changes in the number of workers from weekdays and peak days of visits in the month of the annual tourism event. From the evaluation of the economic generation simulation of community economic activities, it is shown that traders are the most type of business activity in the Menara Kudus religious tourism area and are the most spread in Zone C, where the Menara attractions are located.